To Assess Caregiver Burden of Patients with Dementia: Its Sociodemographic and Clinical Correlates - Vijay Raghuwanshi; Pali Rastogi; Vijay Niranjan; Prashant Maravi; Virendra S. Pal (Archives of Medicine and Health Sciences)
Background and Aim: To assess the primary caregiver burden in the patients of dementia. Dementia is a chronic neurodegenerative disorder that refers to a disease process marked by progressive cognitive impairment in clear consciousness. The morbidities associated with dementia accounts for the poor quality of life. Equally affected are caregivers of these patients. The study aims to assess the caregiver burden (CGB) and how the care of these patients affect them. This further includes sociodemographic and clinical features of the caregivers. Materials and Methods: The cross-sectional study was conducted from June 2021 to May 2022 in the Department of Psychiatry, MGM medical college, Indore (M.P.) after approval from the institutional ethical committee. The study included 60 patients and 60 caregivers attending Psychiatry outpatient department (OPD). They were assessed using a semi-structured proforma consisting of socio-demographic and clinical variables. Clinical rating scale i.e., burden assessment schedule (BAS) was applied for caregivers and dementia severity rating scale (DSRS) for the patients. Pearson's and Spearman's correlation coefficient was applied with P-value < 0.05 considered as significant. Result: The study finds that the mean age of the caregiver is 55.6 ± 10.01 years and that of patient is 69.81± 0.71 years. The mean BAS score is 68.3 ± 11.77. A negative correlation is established between BAS and income of the caregiver and is statistically significant (P < .001), while a positive correlation between BAS and age, number of hospitalization, total duration of illness, and the mean of time spent with the patient during the day and is statistically significant (P < .001). Factors like low income, advancing age, and time spent with the patients in the caregivers had affected the BAS score, and the score was found to be raised. Factors related to the patients affecting the BAS score was total duration of illness and number of hospitalization. Both factors played a key role in the addressed the overall care burden among the caregivers. Conclusion: Factors such as low income, advancing age, and time spent with the patients in the caregivers had affected the BAS score, and the score was found to be raised. Factors related to the patients affecting the BAS score was the total duration of illness and number of hospitalization. Both factors played a key role in the addressed the overall care burden among the caregivers.